The Postcolonial Arabic Novel - Safoi Babana-Hampton (International Institute of Islamic Thought, 2004)
Muhsin Jassim Al-Musawi’s book offers a fresh contribution not only to studies in Arabic literature but also to postcolonial critique, cultural criticism, comparative literature, and cross-cultural studies. Its interest lies in the fact that it introduces a relatively less explored territory in postcolonial thought and cultural criticism: namely, Arabic literature. The attention of many western and non-western scholars in the field has long been directed toward Anglophone literature from South Asia, Japan, Africa, and Canada, and then to Francophone literature from North Africa and the Antilles. In the context of the Arab world, the author also situates the importance of his study in how The Thousand and One Nights, a work whose fate and reception he sees as emblematic of the fate of fiction writing in the Arab world, was received. Just like the novel genre in general, this work only received scholarly interest rather recently, after centuries of neglect and disdain by conservatist Arab scholars and elite culture. Central to postcolonial critique, whose sources and precedents can be traced to the practices and discourses of those writers associated with various intellectual traditions (e.g., poststructuralism, deconstruction, Marxism, feminism, cultural studies) and which has affinities with the literary movement known as postmodernism, is the experience of colonization as a moment of cultural self-consciousness and self-dividedness. This moment generates contradictory and ambivalent identity patterns and subject positions resulting from the encounter with the Other (culture), and emphasizes the constructedness of identity. Al-Musawi transposes these key postcolonial motifs and insights to the realm of Arabic literature in order to reveal important dimensions of the contemporary Arabic novel. Scholarly research on Arabic literature (both within and outside the Arab world) often privileged poetry as an object of study, given its historically prominent place in elite culture and the Arab world’s literary canon. The subject choice of the book is of particular interest, because it targets the Arabic novel as an emerging literary genre, and, by the same token, because of its use of postcolonial analytical concepts to account for this relatively new literary genre’s place in contemporary Arab culture and society ...